Сравнение методологических подходов к измерению уровня бедности - Харченко, Н. (Социология: теория, методы, маркетинг, 2000)
The paper reviews the current methodological approaches to the poverty measuring:
absolute, relative, subjective, deprivation, etc. Special attention is paid to the differences
in poverty level and demographic profile of poor households, which appear as
a result of application of different measuring approaches. The author comes to
conclusion, that combination of different approaches to poverty assessment makes our
perception of poverty in our country more complete and stereoscopic.